2020
DOI: 10.1016/j.jcol.2019.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Role of micronize purified flavonoid fraction and ethanol Graptophyllum pictum extract on experimental anal ulcer healing. Study on Wistar rat

Abstract: Aim of the study  To evaluate the role of micronized purified flavanoid fraction and ethanol Graptophyllum pictum extract in the treatment of anal ulcer. Method  Twenty-eight Wistar rats were randomly allocated into four groups. Groups 2, 3 and 4 the anus were induced with croton oil, but was not induced on group 1. Groups 1 and 2 were treated with normal saline, while groups 3 and 4 were treated with micronized purified flavanoid fraction, and ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In a study for patients with hemorrhoids, with a pre and post-test-only group design, it was reported that GPE reduces the signs and symptoms [15]. In animal studies, inducing anal Wistar rats with croton oil, showed that GPE, reduces inflammatory markers [16], accelerates ulcer healing [17], and reduces edema [18]. Currently, in Indonesia, GPE can be considered a standardized herb.…”
Section: Medicamentous Treatment 61 Flavonoidsmentioning
confidence: 99%
“…In a study for patients with hemorrhoids, with a pre and post-test-only group design, it was reported that GPE reduces the signs and symptoms [15]. In animal studies, inducing anal Wistar rats with croton oil, showed that GPE, reduces inflammatory markers [16], accelerates ulcer healing [17], and reduces edema [18]. Currently, in Indonesia, GPE can be considered a standardized herb.…”
Section: Medicamentous Treatment 61 Flavonoidsmentioning
confidence: 99%